MTOR signaling in the arcuate nucleus of the hypothalamus mediates the anorectic action of estradiol. Issue 3 (September 2018) - González-García, Ismael; Martínez de Morentin, Pablo B; Estévez-Salguero, Ánxela; Contreras, Cristina; Romero-Picó, Amparo; Fernø, Johan; Nogueiras, Rubén; Diéguez, Carlos; Tena-Sempere, Manuel; Tovar, Sulay; López, Miguel
Abstract : Current evidence suggests that estradiol (E2), the main ovarian steroid, modulates energy balance by regulating both feeding and energy expenditure at the central level, through the energy sensor AMP-activated protein kinase (AMPK). We hypothesized that the hypothalamic mechanistic target of rapamycin (mTOR) pathway, a well-established nutrient sensor and modulator of appetite and puberty, could also mediate the anorectic effect of E2. Our data showed that ovariectomy (OVX) elicited a marked downregulation of the mTOR signaling in the arcuate nucleus of the hypothalamus (ARC), an effect that was reversed by either E2 replacement or central estrogen receptor alpha (ERα) agonism. The significance of this molecular signaling was given by the genetic inactivation of S6 kinase B1 (S6K1, a key downstream mTOR effector) in the ARC, which prevented the E2-induced hypophagia and weight loss. Overall, these data indicate that E2 induces hypophagia through modulation of mTOR pathway in the ARC.